Suatu Kajian Literatur: Karakteristik dan Asesmen Pembelajaran Abad 21 tentang Penilaian Autentik - Ari Deca Fitriani; Sigit Prasetyo (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The purpose of this study is to analyze teachers’ understanding of authentic assessment. The assessment process seeks to evaluate whether educational goals have been met, thus highlighting the important role of evaluation in the education sector. Effective and comprehensive evaluation is conducted on an ongoing basis, providing educators with a comprehensive view of student learning achievement and progress. Each subject emphasizes the importance of ongoing assessment, which is aligned with broader educational goals and outcomes. This article serves as a literature review intended to explore the features of 21st century learning and their implications for assessment, specifically authentic assessment. Given globalization and rapid technological advancements, the educational paradigm has shifted from a teacher-centered approach to a student-centered approach. Learning in the 21st century prioritizes the enhancement of critical thinking, creativity, collaboration, and communication skills (often referred to as the 4Cs). Therefore, conventional assessment is considered inadequate to measure learning outcomes that are complex and contextual. This study explores various relevant scientific sources to formulate a comprehensive understanding of authentic assessment as an approach that is in line with the characteristics of 21st century learning. Authentic assessment emphasizes real, contextual processes and products, and provides meaningful learning experiences. The findings of this study recommend that teachers need to design assessments that are integrated with the learning process, encourage active student involvement, and assess abilities holistically. This study is expected to be a guide for education professionals in creating assessment methods that are in line with 21st century requirements.